PENAMPILAN REPRODUKSI SAPI BALI BETINA DENGAN INSEMINASI BUATAN DI KECAMATAN SIDEMEN KABUPATEN KARANGASEM - Nurhalizah S.; N. L. G. Sumardani; I. W. Suberata (Jurnal Peternakan Tropika, 2025)
This study aimed to determine the reproductive performance of female Balinese cattle with artificial insemination in Sidemen District, Karangasem Regency. This study is a survey research using a sample of 51 female Balinese cattle that have given birth at least twice, owned by farmers taken by purposive sampling method in three villages. Data analysis used in this study was quantitative descriptive analysis. Research variables included age at puberty, age at first mating, length of pregnancy, service per conception, and calving interval. The results showed that the reproductive performance of female Balinese cattle with artificial insemination in Sidemen District, Karangasem Regency was good seen from the variable aspects of puberty age 16.64±3.95 months, age of first mating 21.57±3.03 months), gestation length 8.76±0.43 months, service per conception 1.58±0.73 times, and calving interval 15.13±063 months. Based on the results of the study, it can be concluded that the reproductive performance of female Balinese cattle with artificial insemination in Sidemen District, Karangasem Regency is in accordance with the characteristics of reproductive traits of Balinese cattle listed in Ministerial Decree No. 325/Kpts/OT.140/1/2010. ABSTRAK Penelitian ini bertujuan untuk mengetahui penampilan reproduksi sapi bali betina dengan inseminasi buatan di Kecamatan Sidemen, Kabupaten Karangasem. Penelitian ini merupakan penelitian survei menggunakan sampel 51 ekor sapi bali betina yang pernah beranak minimal dua kali, milik dari peternak yang diambil dengan metode purposive sampling di tiga desa. Analisis data yang digunakan dalam penelitian ini yaitu analisis deskriptif kuantitatif. Variabel penelitian meliputi umur pubertas, umur pertama kawin, lama kebuntingan, service per conception, dan calving interval. Hasil penelitian menunjukkan bahwa penampilan reproduksi sapi bali betina dengan inseminasi buatan di Kecamatan Sidemen Kabupaten Karangasem adalah baik dilihat dari aspek variabel umur pubertas 16,64±3,95 bulan, umur pertama kawin 21,57±3,03 bulan, lama kebuntingan 8,76±0,43 bulan, service per conception 1,58±0,73 kali, dan calving interval 15,13±063 bulan. Berdasarkan hasil penelitian maka dapat disimpulkan bahwa penampilan reproduksi sapi bali betina dengan inseminasi buatan di Kecamatan Sidemen Kabupaten Karangasem adalah sesuai dengan karateristik sifat reproduksi sapi bali yang tercantum dalam Kepmenten Nomor 325/Kpts/OT.140/1/2010.